Are the Danish stillbirth rates still record low? A nationwide ecological study. Issue 12 (18th December 2020) - Lidegaard, Øjvind; Krebs, Lone; Petersen, Olav Bennike Bjørn; Damm, Nis Peter; Tabor, A
Abstract : Objectives: After introduction of a more proactive post-term induction practice, stillbirth rates have decreased substantially throughout the first decade of this century in Denmark. The aim was to follow up on induction and stillbirth rates in Denmark. Design: Historical ecological study. Participants: We included all delivering women in Denmark during the period 2007–2018. Intervention: Induction rates from 41 weeks of gestation. Main outcome measure: Stillbirth rates from 41+0 weeks. Results: Of 739 570 delivered children, 179 734 (24.3%) were born from 41+0 weeks. The proportion of deliveries after 41 weeks which were induced increased from 25.4% in 2007 to 44.4% in 2012. From 2012 to 2015, the induction rates decreased from 44.4% to 39.4%. After 2015 rates were stable. During the same period, stillbirth rates decreased from 1.30 in 2007/2008 to 0.38 per 1000 newborn in 2011/12; -54%. From 2012, however, the rates were doubled from 0.38 per 1000 in 2011/2012 to 0.74 per 1000 in 2015/2018; RR 1.97 (95% CI 1.02 to 3.81), p=0.033. Changes in the included potential confounders cannot explain neither the substantial fall in stillbirth rates from 2007/2008 to 2011/2012, nor the doubling in stillbirth rates after 41 weeks since 2012. During the whole study period, the cumulated risk of intrauterine foetal death increased from week 41+0 to 41+6 from 0.16 to 1.25 per 1000 ongoing pregnancies or 7.8 folds. Going beyond 42 weeks further increased the risk to 2.46 per 1000 ongoing pregnancies. Conclusion: We found a consistent inverse correlation between the proportion of women with induction of labour after 41 weeks of gestation and the stillbirth rates during the same period and same gestational ages. This Danish update on post-term inductions and corresponding stillbirth rates thus confirm previous findings suggesting a causal link between these two parameters.